Ecologização do direito internacional humanitário: perspectivas para maior efetividade da proteção ambiental durante conflitos armados. - Ventura, Victor Alencar Mayer Feitosa (2013)
The object of this work is the problem of the effectiveness of International Humanitarian Law (IHL) rules regarding the protection of the environment in times of armed conflict. The phenomenon of the deliberate destruction of natural environment to meet military decisions in war scenarios is being used as a battle strategy that affects the nature, makes it a silent victim and endangers a healthy quality of life for this and future generations. These are graves breaches that face difficult legal enforcement, which were chronicled in recent years, for example, in conflicts in the Gulf (1992), Kosovo (1999), Lebanon (2006) and Palestine (2009). Despite the regulations produced by the instruments of IHL, the effectiveness of these normative acts just hampered by the lack of definition of the legal requirements for establishing the environmental damage resulting from military maneuvers, or the difficulty in meeting the high threshold of existing requirements. The problem arises when part of international literature takes humanitarian system for closed and self-contained, while other authors conceive the possibility of, given its ineffectiveness in protecting nature during hostilities, making it permeable to other special legal regimes such as Human Rights and Environmental Law. For the purposes of this study, given the absence of express incompatibility between the humanitarian and environmental special branches, facing the problem means stimulating greater interaction between the leges speciales of IHL and International Environmental Law, as a way of expanding the canons of nature conservation. Therefore, it sustains the viability of both formal and substantive interaction between these systems in the process of "greening" of humanitarian law, for the purpose of carrying out the protection of the physical environment during armed conflict.